The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0118440
|View full text |Cite|
|
Sign up to set email alerts
|

Individualized Homeopathic Treatment and Fluoxetine for Moderate to Severe Depression in Peri- and Postmenopausal Women (HOMDEP-MENOP Study): A Randomized, Double-Dummy, Double-Blind, Placebo-Controlled Trial

Abstract: BackgroundPerimenopausal period refers to the interval when women's menstrual cycles become irregular and is characterized by an increased risk of depression. Use of homeopathy to treat depression is widespread but there is a lack of clinical trials about its efficacy in depression in peri- and postmenopausal women. The aim of this study was to assess efficacy and safety of individualized homeopathic treatment versus placebo and fluoxetine versus placebo in peri- and postmenopausal women with moderate to sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 51 publications
0
37
0
2
Order By: Relevance
“…Although 1.3% of the general population may use homeopathy for psychiatric symptoms [26], this use is more frequently associated with anxiety disorders than with depression. The evidence for the efficacy of homeopathy in the treatment of depression is limited to moderate to severe depression [27]. The prevalence of subthreshold depression has been receiving increasing attention, however, and has been linked to greater healthcare utilization [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although 1.3% of the general population may use homeopathy for psychiatric symptoms [26], this use is more frequently associated with anxiety disorders than with depression. The evidence for the efficacy of homeopathy in the treatment of depression is limited to moderate to severe depression [27]. The prevalence of subthreshold depression has been receiving increasing attention, however, and has been linked to greater healthcare utilization [28].…”
Section: Discussionmentioning
confidence: 99%
“…1 The results of this study showed, for the first time, that individualized homeopathic treatment (IHT) using 30c and 200c potencies, as well as fluoxetine, was effective in improving depression in climacteric women after a 6-week period of treatment. 2 even though all of the issues of the concern raised during postpublication discussions with the journal were answered by us in full, as well as the overarching point that none of them was sufficiently serious to justify retraction.…”
Section: Introductionmentioning
confidence: 92%
“…The individualized homeopathic consultation (IHC) was carried out according to the "classical" homeopathy methods described in Hahnemann's Organon of Medicine (paragraphs 83-104), stated in the Methods section of the article. 2 During post-publication discussions, we provided a detailed guidance and step-by-step explanation as to how the consultation was carried out. As this technique is the "gold-standard" for the homeopathic prescription in daily practice worldwide, it has also been replicated multiple times in clinical research.…”
Section: Introductionmentioning
confidence: 99%
“…Четырехнедельная терапия армодафинилом (150 мг/д) [43] повышала показатели по Menopause Specific Quality Life (р = 0,0001): вазомоторных симптомов и когнитивной функции, подавленности, печали, плаксивости, анергии, колебаний настроения, усталости. Вызывает сомнение превосходство гомеопатии над флуоксетином и плацебо в рандомизированном исследовании антидепрессивной терапии у мексиканских женщин [44]. По PubMed, Medline выполнен обзор об аугментационной роли гормонотерапии в сочетании с антидепрессантами [45]; не отличаются новизной положения, что 50% женщин климактерического возраста нуждаются в фармакотерапии по снижению симптомов КД, в 30% случаев диагностируется ДР, взаимовлияние депрессивных и личностных расстройств и преморбидная депрессивная предрасположенность ведут к хронизации депрессии.…”
Section: фармакотерапия при кдunclassified